Colour preferences amongts paediatric patients in Perak, Malaysia / Suziyanty Matori - Matori, Suziyanty (2014)
This study is about the colour preferences amongst paediatric patients in Perak. Colour is one of the fundamental elements in the physical healthcare design and environment. It can also help refresh the space and is essential in building healing spaces. While colour does not in itself act as a cure, it does affect our mood. Based on studies focusing on healthy adults, there are many specific colours that cannot be applied in every area of the hospital; however, those findings cannot be applied across-the board to environment for children. Furthermore, when children are sick, they may not perceive their surroundings in the same way as healthy children. The research method applies triangulation of descriptive and experimental approach by adapting Park (2007) model on paediatric ward study in the United States as the framework of the present study. This study introduces the use of 3ds Max Model Simulation as an instrument to create a realistic effect in interior wards rather than Park’s (2007) method, which used a static 1:12 scaled model. In this research, the views of 380 healthy children and 117 unhealthy children were explored, together with the views of architects in order to gauge their colour preference for the paediatric ward at Hospital Raja Permaisuri Bainun (HRPB), Ipoh Perak. The approach is unique in the sense that it was driven by the preferred choice of children between seven to eleven years old through the use of ‘child-friendly’ structured interviews.The results were analysed using the highest mean score in order to identify the most preferred colour among the three groups. The results show that blue is the most preferred colour by children in Malaysia, which is consistent with the results of the studies in the United States